Kegiatan Pelatihan Pembuatan dan Penggunaan QRIS Guna Meningkatkan Sistem Pembayaran Secara Efisien pada Pelaku Usaha Mikro Jeruk Zea Ice, Deltasari Indah, Sidoarjo - Feri Dwi Yulianto; Uswatun Chasanah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
With 65 million entities, micro, small, and medium enterprises (MSMEs) form the backbone of the Indonesian economy, contributing around 61% of the country's gross domestic product (GDP) and employing 97% of the working population. Despite their strategic role, most MSMEs still face various challenges, such as low adaptability to changes in the business environment, lack of planning strategies, minimal innovation, and limitations in utilizing technology. On the other hand, current consumer behavior increasingly demands quality products and practical services, including in terms of payment systems. Along with the development of the digital era, non-cash payment systems, such as e-money and QR codes, have experienced rapid growth and become important elements in encouraging financial inclusion and transaction efficiency. QRIS (Quick Response Code Indonesian Standard) is present as an innovative solution that allows MSMEs to make transactions quickly, safely, and easily by simply scanning a QR code. Realizing the importance of utilizing this technology, the community service (PkM) team conducted training activities on the creation and use of QRIS for the